Performance tolerance and its effect on some functional indicators according to the genetic makeup of the ACTN3 gene in futsal players - Jubair, L.Nouran Aboud; Lahims, Asst.prof.Dr. Hassan Abdelhadi; Jayan, L. Hashim (Sulaimani Journal for Humanities, 2026)
Futsal has gained significant attention from specialists and experts due to its competitive nature and the intensity of its performance, which combines strength and speed in both defense and attack. It has kept pace with all developments in sports science. This study explored scientific methods for reaching advanced levels, highlighting the crucial role of genetics. Our research focuses on one of the most important physical attributes required by both male and female futsal players: the game's specific endurance. Furthermore, the ACTN3 gene is considered vital due to its connection with the indicators and abilities possessed by female futsal players. The problem addressed one of the most significant obstacles in the sports field, a fundamental aspect for engaging in various athletic activities: identifying the appropriate genetic traits for the game through the ACTN3 gene's genetic makeup. This allows for selection based on an individual's specific characteristics, which truly reflect their abilities and are determined by their inherent traits. Genetic and functional indicators provide more objective results than physical or skill-based determinants. The study aimed to identify performance endurance and ACTN3 gene variants and their effect on certain functional variables in futsal players. The research population consisted of futsal Premier League players for the 2022/2023 season. The sample was selected purposively from Premier League clubs, as they include high-caliber players. The main experiment was conducted in two phases: first, blood samples (cc3) were drawn from the players and the gene was analyzed to identify variants; second, a futsal performance endurance test was administered. The most important conclusion was that players with the RX allele, considered a precise indicator and code for players, exhibited higher functional indicators, giving them an advantage over their peers with the RR and XX alleles. This allows them to perform faster and in less time.
Keywords: Functional indicators; genetic makeup; ACTN3